COMT gene polymorphisms, cognitive performance, and physical fitness in older adults. (September 2015) - Voelcker-Rehage, Claudia; Jeltsch, Albert; Godde, Ben; Becker, Sandra; Staudinger, Ursula M.
Abstract: Objective: It is well known that genetic predispositions might influence cognitive performance, particularly in older adults. One gene related to executive functioning is the COMT gene with met/met carriers outperforming val/val carriers in cognitive tasks. Further, it has been shown that fitness is positively related to cognitive functioning in older adults. As both, the COMT genotype and physical exercise have been shown to influence dopamine availability and as changes in dopamine metabolism seem to play a key role in cognitive aging, the aim of this study was to analyze the association of the COMT gene polymorphisms with the relationship between fitness and cognition. Design: We used a cross-sectional design. Method: Sixty-eight healthy older adults between 62 and 79 years of age were analyzed in this study. DNA was extracted from capillary blood samples. Participants performed a modified version of the Flanker Task as an indicator of executive control and a battery of motor and physical tests as indicators of fitness. Results: Hierarchical regression analyses revealed a positive influence of overall fitness and an interactive effect of fitness and COMT polymorphisms on Flanker accuracy performance. Val/val carriers revealed the highest positive correlation between fitness and cognition. Conclusions: Our data suggest that particularly val/val allele carriers benefit from exercise by improved cognitive functioning whereas met/met carriers already perform closer at their optimum level. Highlights: Association of val158met polymorphism in COMT with the relationship between fitness and cognition was analyzed. COMT gene polymorphisms and fitness interact in their association with executive functioning. Particularly val/val carriers seem to benefit from a higher fitness level. A high fitness level might entail optimization of central dopamine availability.